Pengembangan Modul Pembelajaran Berbentuk Pop-Up dan Smash Book Materi Sifat Cahaya Bagi Siswa Penyandang Disabilitas Rungu (UPEJ Unnes Physics Education Journal, 2019)
The aim of this research is to develop an IPA (Physics) learning module in form of pop-up and smash book on Nature of Light that tested it is feasibility, effectiveness, and practicality. This research uses Research and Development methode (R & D). Test design using pre-eksperimental design with one group pretest-posttest. Initial test was conducted at SLB Wantu Wirawan and final test was conducted at SLB Negeri Salatiga. The result show that the module in form of pop-up and smash book on Nature of Light was classified feasible by media validator and material validator with media feasibility percentage 90,50% and material feasibility 85,50%. The effectiveness percentage of module 92,00% with N-Gain 0,64 and practicality percentage 92,50%. Based on the result of this research concluded that module in form of pop-up and smash book was proven feasible, effective, and practical to use by deaf students in IPA (Physics) learning, particularly on Nature of Light